Penggunaan Media Audiovisual Pada Pembelajaran Seni Musik di Kelas VIII A SMPN 35 Kerinci - Pandu Dwi Yanta Putra; Irdhan Epria Darma Putra (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
This study aims to describe the use of Audiovisual Media in Music Arts Learning in class VIII A SMP Negeri 35 Kerinci. The low ability of students to understand music art materials is known to be influenced by the less optimal use of audiovisual media by teachers, which is caused by limited infrastructure facilities and access to technology in schools. This study uses a descriptive qualitative method, where data is collected through observation and assessment of student learning outcomes. The use of this media not only makes it easier for students to understand the material but also increases their activeness in class. The findings of this study confirm that audiovisual media plays an important role in learning music art, especially in improving motivation and learning outcomes. Infrastructure support and access to technology are crucial factors in the effectiveness of the use of this media in teaching and learning activities